Association of Mitochondrial Function, Substrate Utilization, and Anaerobic Metabolism With Age-Related Perceived Fatigability. (14th August 2020) - Liu, Fangyu; Wanigatunga, Amal A; Zampino, Marta; Knuth, Nicolas D; Simonsick, Eleanor M; Schrack, Jennifer A; Ferrucci, Luigi
Abstract: Previous work has shown that poorer mitochondrial function is associated with age-related perceived fatigability. However, whether glucose oxidation and anaerobic metabolism are intermediate factors underlying this association remains unclear. We examined the total cross-sectional association between mitochondrial function and perceived fatigability in 554 adults aged 22–99 years. Mitochondrial function was assessed by skeletal muscle oxidative capacity (kPCr) using 31P magnetic resonance spectroscopy. Perceived fatigability was measured by rating of perceived exertion after a 5-minute (0.67 m/s) treadmill walk. The intermediate role of glucose oxidation (measured by the rate of change of respiratory exchange ratio [RER change rate] during the 5-minute treadmill walk) and anaerobic metabolism (measured by ventilatory threshold [VeT] during a maximal treadmill test) was evaluated by examining their cross-sectional associations with kPCr and perceived exertion. For each 0.01/s lower kPCr, perceived fatigability was 0.47 points higher ( p = .002). A 0.01/s lower kPCr was also associated with 8.3 L/min lower VeT ( p < .001). Lower VeT was associated with higher fatigability at lower levels of kPCr but not at higher kPCr levels (β for interaction = 0.017, p = .002). kPCr and RER change rate were not significantly associated ( p = .341), but a 0.01/min higher RER change rate was associated with 0.12-point higher fatigability ( p = .001). Poorer mitochondrial function potentially contributes to higher perceived fatigability through higher glucose oxidation and higher anaerobic metabolism. Future studies to further explore the longitudinal mechanisms between these metabolic changes and fatigability are warranted.